Preliminary Investigation Of Low-Code/No-Code Ecosystem Practices : Interpreting Students’ Views on the Development Of Interactive Prototype Design - Azwan, Abidin; Azaini, Manaf (Kolokium Komik Digital Malaysia KKDM MYCOMIC-MDEC, 2024)
The low-code/no-code (LCNC) ecosystem practices for interactive prototype design platforms has started to evolved to facilitate the processes of digital transformation by enabling people with non-programming skills to engage in designing digital products. In other words, the ecosystem allows people from non-HCI design background to participate in the design development through intuitive interfaces and pre-build components. Indirectly, the waves of this ecosystem influence learning settings in design education and act as a catalyst for turning design concepts into front-end logical code without coding. The study shows the insights of design students' experiences from LCNC methods during an interactive design course at UNIMAS, Malaysia. This study adopted a qualitative research approach by employing an online survey. This study has shed light on the essential need for a new paradigm in teaching-learning activities in design education, as demonstrated by the growth of LCNC practices that may be integrated in relevant design courses.